"Making the News": a case study of East Cape News (ECN) - Davidow, Audrey Beth (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 1999)
To fully comprehend the complex process of news making, we must first understand that the events we read about everyday in the newspaper are not merely a reflection of the world in which we live. News does not just happen. Rather, it is a socially constructed product in which events are "made to mean" (Hall, 1978). Thus, the news plays a fundamental role in shaping our interpretations of reality - our perceptions of the world as we know it. Informed by a structuralist approach to news making, this research provides a detailed ethnographic study of the determinants that shape and produce news in the South African print media. I provide examples of the influence various factors, operating at all levels, exert within the news making process. The research focuses on the news production process at East Cape News Pty. Ltd. (ECN) a small news agency operating in the peripheral news region of South Africa's Eastern Cape. It considers the journalistic routines and interests of the ECN reporters; how these reporters select events and turn them into news, how they interpret their significance and how they formulate them as news stories. The research also considers the second stage of selection ECN news must pass before it is read by the public - the "gates" of external newspapers. In this section, the study is primarily concerned with which ECN news stories succeed past the gates of national newspapers as these are the newpapers that play an influential role in shaping national perceptions of the marginalised Eastern Cape region. A province burdened with devastating rural poverty, unstable government, and little economic growth, the Eastern Cape warrants little coverage from the national, Johannesburg-based news market. As a result, little news of the Eastern Cape is published nationally, further perpetuating the region's perceived insignificance on a national level. This point also demonstrates the fact that news both shapes, and is shaped by, our ideologies. News, therefore is ideological (Fishman, 1977). My findings reinforce many of the observations of other media researchers informed by a structuralist approach in the field of news making. However, some elements of news making emerge which appear to be unique in terms of other studies of news making. These elements are primarily a result of ECN's informal organisational structures which allow the journalists a greater level of autonomy than a larger more bureaucratic organisation might. Thus, in addition to considering the structures that shape the news, I also discuss the role of human agency in making the news.
Keywords: Reporters and reporting; Reporters and reporting -- South Africa; Attribution of news; News agencies -- South Africa -- Eastern Cape